Effect of Resource Allocation on Project Success in Non-Profit Organizations in the Nigeria - David Mark (International Journal of Project Management, 2024)
Purpose: The aim of the study was to assess the effect of resource allocation on project success in non-profit organizations in the Nigeria. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study found that when resources, including financial, human, and technological assets, are strategically distributed, organizations can better achieve their objectives and maximize impact. For instance, optimal financial management allows non-profits to fund essential programs and services, while adequate staffing enhances project implementation through diverse skills and perspectives. Moreover, the alignment of resources with project goals fosters greater stakeholder engagement, resulting in improved collaboration and support. Ultimately, effective resource allocation not only contributes to immediate project outcomes but also strengthens the long-term sustainability and growth of non-profit organizations, enabling them to adapt to changing community needs and challenges. Implications to Theory, Practice and Policy: Resource-based view (RBV), theory of constraints (TOC) and systems theory may be used to anchor future studies on assessing the effect of resource allocation on project success in non-profit organizations in the Nigeria. In the realm of practical implementation, organizations are encouraged to initiate pilot projects aimed at testing Blockchain applications in targeted supply chain processes. In the policy domain, collaboration with policymakers is vital to develop clear and supportive regulatory frameworks for Blockchain adoption in supply chains.